# Case

### From HaskellWiki

(Difference between revisions)

(one colon too much) |
(→Using functions: reshuffle some code lines, c/e) |
||

(9 intermediate revisions by 4 users not shown) | |||

Line 1: | Line 1: | ||

+ | == Question == | ||

+ | |||

Can I have a <hask>case</hask> where the alternatives contain expressions? | Can I have a <hask>case</hask> where the alternatives contain expressions? | ||

+ | == Answer == | ||

− | + | There are several approaches to this problem. | |

− | + | === Using functions === | |

− | + | ||

− | + | ||

− | + | ||

− | + | ||

− | + | ||

− | + | ||

− | + | ==== select ==== | |

− | + | We can do this nicely with a function implemented in Haskell: | |

<haskell> | <haskell> | ||

select :: a -> [(Bool, a)] -> a | select :: a -> [(Bool, a)] -> a | ||

select def = maybe def snd . List.find fst | select def = maybe def snd . List.find fst | ||

− | + | -- = fromMaybe def . lookup True | |

+ | -- = maybe def id . lookup True | ||

select exDefault | select exDefault | ||

Line 25: | Line 23: | ||

(cond3, ex3)] | (cond3, ex3)] | ||

</haskell> | </haskell> | ||

+ | Unfortunately this function is not in the [[Prelude]]. | ||

+ | It is however in the [http://hackage.haskell.org/packages/archive/utility-ht/0.0.1/doc/html/Data-Bool-HT.html#v%3Aselect utility-ht] package. | ||

+ | |||

+ | ==== nested 'if' ==== | ||

Alternative implementations are | Alternative implementations are | ||

<haskell> | <haskell> | ||

− | |||

− | |||

{- a purely functional implementation of if-then-else -} | {- a purely functional implementation of if-then-else -} | ||

if' :: Bool -> a -> a -> a | if' :: Bool -> a -> a -> a | ||

Line 39: | Line 39: | ||

The implementation of <hask>select''</hask> makes clear that <hask>select</hask> can be considered as nested <hask>if</hask>s. | The implementation of <hask>select''</hask> makes clear that <hask>select</hask> can be considered as nested <hask>if</hask>s. | ||

The functional <hask>if'</hask> is also useful in connection with <hask>zipWith3</hask> since <hask>zipWith3 if'</hask> merges two lists according to a list of conditions. | The functional <hask>if'</hask> is also useful in connection with <hask>zipWith3</hask> since <hask>zipWith3 if'</hask> merges two lists according to a list of conditions. | ||

+ | See [[if-then-else]]. | ||

+ | Alternatively you can unroll <hask>foldr</hask> and write | ||

+ | <haskell> | ||

+ | if' cond1 ex1 $ | ||

+ | if' cond2 ex2 $ | ||

+ | if' cond3 ex3 $ | ||

+ | exDefault | ||

+ | </haskell> | ||

− | If you | + | ==== infix operator ==== |

+ | |||

+ | If you use <hask>if'</hask> in infix form, | ||

+ | you may call it <hask>?</hask> like in C, | ||

+ | then because of partial application it will work nicely together with '$' for the else clause. | ||

<haskell> | <haskell> | ||

− | + | infixl 1 ? | |

− | + | (?) :: Bool -> a -> a -> a | |

− | + | (?) = if' | |

− | + | ||

− | + | cond1 ? ex1 $ | |

− | + | cond2 ? ex2 $ | |

+ | cond3 ? ex3 $ | ||

+ | exDefault | ||

+ | </haskell> | ||

+ | === Using syntactic sugar === | ||

− | + | ==== Guards ==== | |

− | + | ||

− | + | You can make use of some [[syntactic sugar]] of Haskell, namely of [[guard]]s. | |

− | + | ||

+ | <haskell> | ||

+ | case () of _ | ||

+ | | cond1 -> ex1 | ||

+ | | cond2 -> ex2 | ||

+ | | cond3 -> ex3 | ||

+ | | otherwise -> exDefault | ||

+ | </haskell> | ||

+ | |||

+ | Alternatively, one could simply factor out a function(/value) and use guards in the argument patterns. | ||

+ | |||

+ | ==== List comprehensions ==== | ||

+ | |||

+ | An alternative sugarful approach is to use [[list comprehension]]s. | ||

+ | |||

+ | <haskell> | ||

+ | head $ | ||

+ | [ ex1 | cond1 ] ++ | ||

+ | [ ex2 | cond2 ] ++ | ||

+ | [ ex3 | cond3 ] ++ | ||

+ | [ exDefault ] | ||

</haskell> | </haskell> | ||

+ | [[Category:FAQ]] | ||

[[Category:Idioms]] | [[Category:Idioms]] |

## Latest revision as of 18:31, 15 March 2012

## Contents |

## [edit] 1 Question

Can I have acase

## [edit] 2 Answer

There are several approaches to this problem.

### [edit] 2.1 Using functions

#### [edit] 2.1.1 select

We can do this nicely with a function implemented in Haskell:

select :: a -> [(Bool, a)] -> a select def = maybe def snd . List.find fst -- = fromMaybe def . lookup True -- = maybe def id . lookup True select exDefault [(cond1, ex1), (cond2, ex2), (cond3, ex3)]

Unfortunately this function is not in the Prelude. It is however in the utility-ht package.

#### [edit] 2.1.2 nested 'if'

Alternative implementations are

{- a purely functional implementation of if-then-else -} if' :: Bool -> a -> a -> a if' True x _ = x if' False _ y = y select'' = foldr (uncurry if')

select''

select

if

if'

zipWith3

zipWith3 if'

See if-then-else.

Alternatively you can unrollfoldr

if' cond1 ex1 $ if' cond2 ex2 $ if' cond3 ex3 $ exDefault

#### [edit] 2.1.3 infix operator

If you useif'

?

then because of partial application it will work nicely together with '$' for the else clause.

infixl 1 ? (?) :: Bool -> a -> a -> a (?) = if' cond1 ? ex1 $ cond2 ? ex2 $ cond3 ? ex3 $ exDefault

### [edit] 2.2 Using syntactic sugar

#### [edit] 2.2.1 Guards

You can make use of some syntactic sugar of Haskell, namely of guards.

case () of _ | cond1 -> ex1 | cond2 -> ex2 | cond3 -> ex3 | otherwise -> exDefault

Alternatively, one could simply factor out a function(/value) and use guards in the argument patterns.

#### [edit] 2.2.2 List comprehensions

An alternative sugarful approach is to use list comprehensions.

head $ [ ex1 | cond1 ] ++ [ ex2 | cond2 ] ++ [ ex3 | cond3 ] ++ [ exDefault ]